CHANGES OF INNATE IMMUNITY INDEXES IN SEVERE ASTHMA IN CHILDREN - L. V. Gankovskaya; L. S. Namazova-Baranova; G. V. Poriadin; V. V. Grechenko; V. A. Gankovsky; A. A. Alekseeva; Zh. M. Salmashi; A. N. Kazimirsky; B. G. Bragvadze; O. A. Svitich (Медицинская иммунология, 2019)
At the present time, the role of innate immunity in pathogenesis of bronchial asthma (BA) is actively studied, in particular, significance of TLRs and cytokines. The study included 42 patients with severe bronchial asthma (from 3 to 12 years old), and 67 healthy children at the same age. Expression of TLR2, TLR4, and TLR9 genes was evaluated by PCR-RT from the scrapings of nasal mucosa; cytokines (IL-33, TSLP, IL-4, TGF-β1 and IL-28B) were assayed in nasal swabs by ELISA technique. The main results were as follows: an increased gene expression of TLR2, TLR4, TLR9 genes was revealed in the nasal mucosa scraps from the patients with bronchial asthma as compared to healthy children. We have also measured the contents of important cytokines secreted by the respiratory epithelium in the course of TLRs activation. The study of IL-33, TSLP, IL-4 in nasal samples revealed significantly increased concentrations of these cytokines in the patients with severe BA against the control group. A study of TGF-βlevels in nasal cavity swabs revealed a significant decrease of this regulatory cytokine in the group of pediatric patients with asthma. Worth of note, evaluation of antiviral IL-28B cytokine in the group of patients with severe BA showed a significant downward trend, in comparison to the control indexes. Hence, one may conclude on some disturbances of local innate immunity system in the patients with severe BA which manifest as hyperexpression of TLRs genes, increased production of proinflammatory and epithelial cytokines, decreased production of antiviral IL-28B cytokine, and TGF-β1.